PENGARUH RISIKO PERBANKAN, KEBIJAKAN MONETER, DAN INFLASI TERHADAP PROFITABILITAS BANK KBMI - Bagus Dwi Budiman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The profitability of banks was affected by the COVID-19 pandemic, which also impacted even the larger banks. Further examination of the previous period revealed that the profitability of major banks between 2014 and 2021 tended to be stagnant and even experienced a decline. This study aims to determine the influence of banking risks, including credit risk (NPL), liquidity risk (CR), market risk (NIM), and operational risk (BOPO), as well as macroeconomic factors like the SBDK (Loan to Deposit Ratio) and inflation on bank profitability measured by Return on Assets (ROA). The data used in this study is secondary data, and the data collection method is documentation. The population consists of 4 banks from KMBI 4 and 9 banks from KBMI 3, observed over an 8-year period from 2014 to 2021. The research analysis method used is multiple linear regression analysis with a panel data model. The research results indicate that credit risk (NPL) has a significant influence only on the profitability of bank KBMI 4. Operational risk (BOPO) and market risk (NIM) have a significant impact on the profitability of both bank KBMI 4 and KBMI 3. On the other hand, liquidity risk (CR), SBDK, and inflation do not have a significant influence on the profitability of bank KBMI 4 and KBMI 3.